Adaptation, Further Elaboration, and Validation of a Scale to Measure Hope as Perceived by People: Discriminant Value and Predictive Utility Vis-à-Vis Dispositional Hope. (December 2019) - Krafft, Andreas M.; Martin-Krumm, Charles; Fenouillet, Fabien
Against the background of different psychological conceptualizations of hope, this article elaborates and validates a measure to assess hope as perceived by the general public adapting it from the hope and optimism subscale of the World Health Organization Quality of Life Spirituality, Religion and Personal Beliefs Questionnaire. The results presented here are part of a yearly Internet-based cross-sectional survey in Germany and Switzerland called Hope-Barometer, from which 4 samples of 3 different years with about 17, 500 participants have been used. Following the results of exploratory and confirmatory factor analyses as well as convergent validity, discriminant value, and predictive utility, our findings suggest that the six items of the resulting Perceived Hope Scale exhibits robust psychometric properties, and that perceived hope is distinct and broader than dispositional hope, in which it relates not only to cognitive but also to spiritual, religious, and altruistic dimensions.